Financial management behavior of Indonesian banking customer based on individual literacy level - Agustina, Yuli; Davis, Charlotte; Haryono, Shabilla Berliana (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
The purpose of this study is to examine the relationship between financial literacy, educational attainment, and income level and financial management behavior. Individuals must demonstrate excellent financial management abilities in order to avoid financial difficulties. The level of financial literacy can be used to assess financial management behavior. Along with financial literacy, there are educational and income levels to consider. As a result, the researchers included variables for education level and income level. Customers of the BRI bank branch in Madiun City were included in this study. The sample consisted of 205 respondents who were chosen through a process known as purposive sampling. The study gathered data from primary and secondary sources. Primary data were collected from respondents through a questionnaire, while secondary data were gathered from the literature. Structural Equation Modeling (SEM) was used to process the data in this study, along with the SmartPLS application program. This study found that financial literacy positively impacts financial management behavior. On the other hand, neither education nor income has an effect.